Theorie optimaler Währungsräume vor dem Hintergrund der EU-Erweiterung - Heiko Peters (Westfälische Wilhelms-Universität Münster, Institut für Ökonomische Bildung (IÖB), 2006)
The first step towards integration of the ten new member countries of the European Union was their accession. The second step will be their integration into the European Monetary Union. Here, they have to give up their own monetary policy in favour of complying with the monetary policy of the European Central Bank. The exchange rate as a shock absorber is not available anymore. The expected costs of accession to a monetary union are typically derived by optimum currency area theory. According to optimum currency area theory one can divide the new member countries into two groups. For the first group - Slovenia, Czech Republic, Hungary, Cyprus and Malta - the accession costs are lower than for the second group - Poland, Latvia, Lithuania, Estonia and Slovakia. So the accession of the second group should be postponed until a stronger economic adjustment toward the European Monetary Union is reached.
Keywords: 330; Optimaler Währungsraum; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Theorie; EU-Staaten